Clinical Outcomes of Neuromyelitis Optica with Brain Magnetic Resonance Imaging Abnormalities - hengqi Lu; Yanxia Huang; Lei Zhang; Yinyao Lin; Yanqiang Wang; Bingjun Zhang; Xuejiao Men (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2015)
Objective: To investigate clinical outcomes of neuromyelitis optica (NMO) patients with brain magnetic resonance imaging (MRI) abnormalities. Methods: One hundred and thirty-seven patients with NMO were enrolled. Clinical, laboratory, and MRI features were assessed and compared according to different distribution patterns of brain lesions. Results: The relapse number, Expanded Disability Status Scale (EDSS) score at initial diagnosis, and EDSS score at last visit were significantly higher in NMO patients with brain abnormalities than those in NMO patients without brain abnormalities, respectively. NMO patients with brainstem involvement had higher relapse number, EDSS score at initial diagnosis, and EDSS score at last visit than those without brain abnormalities or with only suprotentorial lesions. Conclusions: Appearance of brain abnormalities in the initial stage, especially brainstem involvement, might be a predictor of severe neurologic deficits and poor prognosis in NMO.